PENGARUH MOTIVASI BELAJAR DAN MEDIA BELAJAR DIGITAL TERHADAP KEMAMPUAN BAHASA INGGRIS - Euis Meinawati; Eni Irfiani (Paradigma, 2016)
This study aims to determine the effect of learning motivation and learning media toward English language proficiency. The method used in the study is an experiment with a 2x2 factorial design. The technique used to analyze the data in this study is the technique of analysis of variance (ANOVA) 2 lanes at significance level α = 0.05 and α = 0.01. If the analysis is found in the interaction, then followed by Tuckey test. Normality test conducted using the test Liliefors, while the homogeneity test using Bartlett's test with a confidence level of α = 0.05. The results showed that there were differences between the groups of English learning students learn to use digital games and movies for Fh (k) = 8,130 to Ft (0,05) = 4:04 (Fh (k)> Ft), then there is an interaction effect between English language learning with digital games and movies for Fh (bxk) = 26 168, with Ft (0,05) = 4:04 (Fh (k)> Ft), there are differences in English proficiency among students studying with digital games and learning with film on the group of students who have high motivation because the Q value of count is 9617, with Q table at significant level 5% the amount was 2.86, and that there was no difference between the English skills of students studying with digital games and learning with the film on group of students who have low motivation for the Q value of count is 0839 with the Q table at significant level of 5% was 2.86 magnitude. Keyword: English Language,  Learning Motivation, Learning Digital Media